PENGARUH SELF EFFICACY, SELF ESTEEM, DAN SISTEM PENGUKURAN KINERJA TERHADAP MOTIVASI INSTRINSIK PADA KARYAWAN BANK BUMN DI JAYAPURA (Studi Pada Instalasi Farmasi Kabupaten Dinas Kesehatan Kabupaten Pegunungan Bintang) - Damanik, Berlinda Shari; Rofingatun, Siti; Patma, Kurniawan (Fakultas Ekonomi, Universitas Cenderawasih, 2020)
This study aims to examine the effect of self-efficacy, self-esteem, and performance measurementsystems on the intrinsic motivation of state-owned bank employees in Jayapura. This research data was obtained using primary data by distributing questionnaires onlinedue to the covid-19 outbreak in Indonesia globally to 105 employees of Bank X in Papua, out of 144people/employees. The analysis method used is the Structure Equation Model (SEM) withthe Partial Least Square (PLS) method. The sampling method used snowball sampling in which thesample was initially small in number, then the sample was asked to choose its friends as the sample.It's like a snowball rolling, getting bigger and bigger. The results of this research variable indicate that (1) Self Efficacy has a positive andinsignificant effect on Intrinsic Motivation with p-values (0, 148> 0, 05), (2) Self Esteem has apositive and significant effect on Intrinsic Motivation with p-values (<0, 001 <0, 05), and (3) thePerformance Measurement System has a positive and significant effect on Intrinsic Motivationwith p-values (<0, 001 <0, 05).